2008
DOI: 10.1136/jnnp.2008.151555
|View full text |Cite
|
Sign up to set email alerts
|

Serum homocysteine levels in relation to clinical progression in multiple sclerosis

Abstract: Serum total homocysteine levels are associated with several measures of disease progression in MS but are not elevated in patients with MS compared with controls. The association of homocysteine levels with cognition in patients with progressive MS raises the question of whether homocysteine directly impacts on MS or reflects a more general neurodegenerative process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 32 publications
(38 reference statements)
0
46
0
1
Order By: Relevance
“…17 Interestingly, homocysteine levels may increase in patients with MS compared with healthy patients, while vitamin B 12 or folate levels remain unaffected. [18][19][20][21] However, not all studies have demonstrated a relationship between elevated serum homocysteine and MS. 22,23 The association between B-vitamin deficiency and elevated homocysteine levels in MS might indicate that higher levels of homocysteine play a role in the etiology of MS. This study aimed to examine the relationship between homocysteine, vitamin B 12 , folate and MS by conducting a meta-analysis of case-control studies.…”
Section: Introductionmentioning
confidence: 98%
“…17 Interestingly, homocysteine levels may increase in patients with MS compared with healthy patients, while vitamin B 12 or folate levels remain unaffected. [18][19][20][21] However, not all studies have demonstrated a relationship between elevated serum homocysteine and MS. 22,23 The association between B-vitamin deficiency and elevated homocysteine levels in MS might indicate that higher levels of homocysteine play a role in the etiology of MS. This study aimed to examine the relationship between homocysteine, vitamin B 12 , folate and MS by conducting a meta-analysis of case-control studies.…”
Section: Introductionmentioning
confidence: 98%
“…33 and 41) and accelerates the progression of atherosclerosis (10). Hcy increases blood-brain barrier permeability (12,17) and is a risk factor for neurodegenerative disease (25,34,35), especially Alzheimer disease (AD) (6,19,31). Even mildly elevated Hcy (Ͼ14 mol/l) creates a twofold increase in risk of AD with a significant correlation between blood Hcy concentration and cognitive impairment (8,31).…”
mentioning
confidence: 99%
“…All these mechanisms have been shown to be relevant in the pathogenesis or progression of several neurodegenerative disorders, including MS [47,51]. Teunissen et al [9] have reported that serum total HCSH is probably associated with disease progression. However, their results have not shown significantly higher HCSH levels in patients with MS in comparison to controls.…”
Section: Applicability Of the Methodsmentioning
confidence: 98%
“…Myelin damage disrupts communication between the brain and the rest of the body [5]. Some studies demonstrated elevated plasma HCSH in MS patients [6][7][8], but in others there were no differences [9,10]. Since these amino acids are chiral, enantiomeric analysis of human samples may be desirable for a better understanding the role of metabolism and dynamics of HCSH in humans.…”
Section: Introductionmentioning
confidence: 99%